The Belief in Immortality and the Worship of the Dead, Volume 1 (of 3) : The Belief Among the Aborigines of Australia, the Torres Straits Islands, New Guinea and Melanesia - Frazer, James George, 1854-1941 (Salt Lake City, UT : Project Gutenberg, 2006)
"The Belief in Immortality and the Worship of the Dead, Volume 1" by J. G. Frazer is a scholarly treatise on anthropology and religious studies written in the early 20th century. This first volume focuses specifically on the beliefs surrounding immortality and the cult of the dead as observed among aboriginal communities in Australia, the Torres Straits Islands, New Guinea, and Melanesia. The work delves into the profound influence that these beliefs exert on human life, seeking to elucidate their origins, practices, and cultural meanings. At the start of the text, Frazer outlines the scope and methodology of his lectures, which were originally delivered at St. Andrews. He introduces the historical method of inquiry into religious beliefs, distancing his approach from dogmatic or philosophical discussions. The opening portion lays the groundwork for exploring the concept of immortality, emphasizing the necessity of understanding primitive religious ideas. He discusses how various communities perceive death, the afterlife, and their dead, positing that the worship of spirits is a universal aspect of human culture that has persisted through time. Frazer also highlights the need to study these primitive beliefs as they are rapidly fading in contemporary society, with the aim of preserving knowledge about humanity's shared past. (This is an automatically generated summary.)
Release date is 2006-12-15
E-text prepared by Marilynda Fraser-Cunliffe, David King, and the Project Gutenberg Online Distributed Proofreading Team (http://www.pgdp.net/) from page images generously made available by the Humanities Text Initiative (http://www.hti.umich.edu/), a unit of the University of Michigan's Digital Library Production Service
Keywords: Immortality -- Comparative studies; Ancestor worship -- Oceania; Funeral rites and ceremonies -- Oceania; Burial; Oceania -- Religion; Oceania -- Social life and customs